Analisis Teoretis Model Pembelajaran Bacaan Al-Qur’an Berbasis Audio-Lingual Approach. - Ikhwanuddin, Muhammad (ILJ: Islamic Learning Journal, 2025)
This study explores the theoretical and pedagogical integration of the Audio-Lingual Approach (ALA) in Qur’anic reading instruction within tahfidz institutions, emphasizing its behavioral foundations and spiritual dimensions. The research aims to analyze how the core principles of ALA—habit formation, mimicry, and reinforcement—can be applied to enhance phonetic accuracy and learning effectiveness in Qur’anic recitation. Employing a qualitative library research design, this study synthesizes recent scholarly literature from Sinta- and Scopus-indexed journals, focusing on theoretical models, comparative pedagogies, and empirical findings related to ALA-based instruction. The results indicate that structured repetition, imitation, and positive reinforcement significantly improve articulation precision and long-term memory stability among learners. Furthermore, the integration of external reinforcement with intrinsic spiritual motivation forms a behavioristic-spiritual learning framework that harmonizes technical efficiency with religious meaning. Therefore, this study contributes to the development of a hybrid Qur’anic pedagogy that aligns traditional talaqqi-musafahah practices with modern behavioral learning theories. The findings suggest that future research should examine the practical implementation of the hybrid ALA model in digital or blended learning environments across Islamic educational settings.